Stormskador i lärk och gran : en jämförelse efter stormen Gudrun - Zetterberg, Jonas (SLU/Southern Swedish Forest Research Centre, 2007)
The storm Gudrun January 8-9 2005 felled about 70 millions cubic metres forest in southern Sweden. The majority of the wind damaged forest was spruce (Picea abies). In order to decrease the risk of wind damages in the future other trees species are of interest for forestry in southern Sweden.